CICERO, PHILIPPICS 9.5 AND THE PORTICUS OCTAVIA. (26th October 2016) - Tansey, Patrick
Abstract : On or shortly after 4 February 43b.c. Cicero delivered the Ninth Philippic in an effort to persuade the Senate to honour Ser. Sulpicius Rufus ( cos . 51). He argued that Sulpicius, who had died of natural causes while acting as the Senate's envoy, was nevertheless entitled to the same recognition as legati killed ob rem publicam . In the course of the speech Cicero discussed various historic precedents, including Cn. Octavius ( cos . 165) who was assassinated in Syria in 162b.c. while doing the Senate's bidding and was consequently honoured with a statue on the rostra. The statue was still extant in 43b.c. and Cicero reminded his audience that it was now the only memorial to this great family. Cicero's observation has unanimously been interpreted as signifying that the family of the consul of 165b.c. was extinct in February 43b.c. In fact, Cicero actually meant that the statue on the rostra was now the sole surviving monument associated with the family of Cn. Octavius because the other two monuments that had served as a concrete reminder of the family had latterly been destroyed.